Molding sand powder for casting and processing technology thereof
By using hydrophobic bentonite, coal powder, modified calcium silicate and anionically modified starch, the problems of high moisture content and low compaction rate of molded sand powder for casting are solved, and the effect of improving the strength and wet pressure strength of molded sand powder is achieved.
Patent Information
- Application Number
- CN202510083442.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The existing casting molded sand powder has too high moisture content, which leads to dilution and softening of the clay film, low compaction rate, and inability to effectively coat, resulting in a decrease in wet pressure strength.
Hydrophobic bentonite, coal powder, silicate and anion modified starch are used as the main components, and calcium silicate is modified to reduce the moisture content of the molded sand powder by introducing hydrophobic components and improve the compaction rate.
Effectively reduce the moisture content of the sand powder, improve the compaction rate and wet pressure strength, and ensure that the strength of the sand powder when used meets the requirements.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of casting industry, and in particular relates to casting sand powder and a processing technology thereof. Background Art
[0002] Sand casting refers to the casting method of producing castings in sand molds. Steel, iron and most nonferrous alloy castings can be obtained by sand casting. Since the molding materials used in sand casting are cheap and easy to obtain, the mold is simple to manufacture, and it can adapt to the single-piece production, batch production and mass production of castings, it has long been the basic process in casting production. The quality of castings produced by sand casting is closely related to the quality of the molding sand powder. If the quality of the molding sand powder is not good, a large number of casting waste will be caused. Statistics show that the cost of molding and core making accounts for half of the casting cost. 60% of the casting waste is caused by molding and core making factors. 70% of the defects of casting welding repairs are related to molding and core making materials.
[0003] The quality of the molding sand powder has a crucial impact on the quality of castings produced by casting. The existing ordinary casting sand powder has too high water content, which will cause dilution and softening of the clay film. At the same time, the molding sand powder has a low compaction rate and cannot be well coated, resulting in reduced wet compressive strength.
[0004] Therefore, how to modify the components of the molding sand powder, introduce hydrophobic components, effectively reduce the water content of the molding sand powder, and increase the compaction rate to ensure that the strength of the molding sand powder can meet the requirements when used has become a direction that needs to be focused on. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a casting sand powder and a processing technology thereof, aiming to solve the problems that the existing casting sand powder has too high water content, causing dilution and softening of the clay film, and at the same time, the compaction rate of the casting sand powder is low, which cannot be well coated, resulting in reduced wet compressive strength.
[0006] The present invention uses hydrophobic bentonite, coal powder, silicate and starch as main components, and performs modification treatment on calcium silicate, and uses it together with anion-modified starch. By introducing the hydrophobic component, the water content of the molding sand powder is effectively reduced, and the compaction rate is improved, so as to ensure that the strength of the molding sand powder can meet the requirements when it is used.
[0007] The technical solution of the present invention is as follows:
[0008] The first aspect of the present invention provides a foundry sand powder, which comprises, by weight: 60 to 70 parts of hydrophobic bentonite, 15 to 26 parts of coal powder, 5 to 10 parts of silicate, and 3 to 8 parts of starch.
[0009] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0010] As a preferred technical solution of the present invention, the preparation method of the hydrophobic bentonite is:
[0011] In parts by weight, 30 parts of bentonite and 5 parts of hexadecyltrimethylammonium bromide are added to 200 parts of deionized water, stirred evenly, and then oscillated at 150 r / min for 4 hours at 60° C. using a constant temperature digital oscillator. After the oscillation is completed, centrifugation is performed, and the centrifugal precipitate is dried at 50° C. for 12 hours and ground to obtain hydrophobic bentonite.
[0012] After conventional bentonite is modified with hexadecyltrimethylammonium bromide cationic modifier, the hexadecyltrimethylammonium bromide is combined with the surface of bentonite particles, changing the surface of bentonite particles from hydrophilic to hydrophobic, reducing affinity for water, and effectively reducing the water content of molding sand powder.
[0013] As a preferred technical solution of the present invention, the silicate is selected from any one of magnesium silicate, calcium silicate, aluminum silicate, and iron silicate, or a combination of at least two of them.
[0014] As a preferred technical solution of the present invention, the calcium silicate is modified calcium silicate; the preparation method of the modified calcium silicate is:
[0015] (1) In parts by weight, 10 parts of calcium silicate are added to 100 parts of deionized water, and the mixture is stirred for 0.5 h to obtain a suspension. A hydrochloric acid solution having a mass concentration of 5% is added dropwise to the suspension, and the mixture is reacted at a pH of 5 for 2 h. After the reaction is completed, the mixture is filtered, and the filter residue is dried to obtain acidified calcium silicate.
[0016] (2) In parts by weight, 10 parts of acidified calcium silicate were added to 150 parts of anhydrous ethanol and dispersed evenly, and then 30 parts of ammonia water and 20 parts of deionized water were added, stirred for 0.5 h, and then 6 parts of dodecyltriethoxysilane were added, and the mixture was reacted at 80° C. for 6 h. After the reaction was completed, the mixture was filtered, and the product was washed three times by centrifugation with anhydrous ethanol and vacuum dried at 60° C. for 12 h to obtain modified calcium silicate.
[0017] By pretreating calcium silicate with hydrochloric acid, a large number of silanol groups can be stimulated to form acidified calcium silicate on the surface of calcium silicate. The rich silanol groups in the acidified calcium silicate can undergo a grafting reaction, and the low surface energy substance dodecyltriethoxysilane can be introduced for microencapsulation modification. Dodecyltriethoxysilane forms hydrophobic groups on the surface of calcium silicate particles and is coated on the surface of calcium silicate particles with a nanolayer structure, which greatly increases the contact angle of the modified calcium silicate, improves the hydrophobic performance, and reduces the water content of the molding sand powder.
[0018] As a preferred technical solution of the present invention, the starch is anion modified starch; the preparation method of the anion modified starch is:
[0019] In parts by weight, 10 parts of α-starch and 15 parts of triethanolamine were weighed and added to 100 parts of deionized water, stirred and dissolved for 1 hour, and then 0.5 parts of epichlorohydrin were added to react for 2 hours. After the reaction was completed, 6 parts of acrylic acid and 0.2 parts of ammonium persulfate were added, and the mixture was reacted at 70°C for 4 hours to obtain a starch mixture. 1 part of 3-sulfopropyl hexadecyldimethylammonium, 0.5 parts of calcium chloride, and 7.5 parts of epichlorohydrin were added to the starch mixture, and the mixture was reacted at 60°C for 10 hours. After the reaction was completed, the mixture was filtered and the filter residue was dried to obtain anionic modified starch.
[0020] Anionic modified starch carries negatively charged groups, while hexadecyltrimethylammonium bromide in hydrophobic bentonite carries a strong positive charge. The two attract each other to form a complex, increase hydrogen bonding points, and form a strong bond, thereby increasing the strength and compactness of the molding sand powder. In addition, anionic starch contains amino and carboxyl groups, which can react with the silanol groups in modified calcium silicate to form an interconnected network structure, thereby increasing the area of the bonding bridge and improving the strength and compactness of the molding sand powder.
[0021] A second aspect of the present invention provides a process for processing casting sand powder, comprising the following steps:
[0022] The hydrophobic bentonite, coal powder, silicate and starch are sequentially added into a roller sand mixer to form a semi-finished product, and a mixture is obtained after stirring. The mixture is crushed into 200-300 meshes, and the crushed mixture is packaged to obtain molding sand powder for casting.
[0023] Preferably, the stirring time is 0.2 to 0.5 h.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The present invention performs hydrophobic modification on bentonite and introduces modified calcium silicate having a hydrophobic group, thereby changing the surface of an important component of the molding sand powder from hydrophilic to hydrophobic, thereby reducing the affinity for water and effectively reducing the water content of the molding sand powder.
[0026] (2) The anionic modified starch of the present invention can serve as a bridge to connect the hydrophobic bentonite and the modified calcium silicate. On the one hand, the negatively charged groups of the anionic modified starch are complexed with the positive charges of the hydrophobic bentonite. On the other hand, the amino and carboxyl groups in the anionic starch can be combined with the silanol groups in the calcium silicate to form a network interpenetrating structure, which reduces the fluidity of each component in the molding sand powder, increases the volume shrinkage, and effectively improves the compaction rate. At the same time, the network interpenetrating structure can also serve as a support for the molding sand powder, thereby increasing the wet compressive strength. DETAILED DESCRIPTION
[0027] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0028] The sources of some components in the embodiments and comparative examples are as follows:
[0029] Bentonite, CAS No. 1302-78-9; coal powder, JYP-2107070154, purchased from Shanghai Baoding Energy Co., Ltd.; calcium silicate, CAS No. 10101-39-0; α-starch, CAS No. 9005-84-9.
[0030] Preparation of hydrophobic bentonite: In parts by weight, 30 parts of bentonite (CAS No. 1302-78-9) and 5 parts of hexadecyltrimethylammonium bromide (CAS No. 57-09-0) are added to 200 parts of deionized water, stirred evenly, and oscillated at 150 r / min for 4 hours at 60° C. using a constant temperature digital oscillator. After the oscillation is completed, centrifugation is performed. After the centrifugation is completed, the precipitate is dried at 50° C. for 12 hours, and the hydrophobic bentonite is obtained after grinding.
[0031] Preparation of modified calcium silicate: (1) In parts by weight, 10 parts of calcium silicate (CAS No. 10101-39-0) were added to 100 parts of deionized water, stirred for 0.5 h to obtain a suspension, a hydrochloric acid solution with a mass concentration of 5% was added dropwise to the suspension, and the mixture was reacted for 2 h at a pH of 5. After the reaction was completed, the mixture was filtered and the residue was dried to obtain acidified calcium silicate. (2) In parts by weight, 10 parts of acidified calcium silicate were added to 150 parts of anhydrous ethanol (CAS No. 64-17-5) and dispersed uniformly, and then 30 parts of ammonia water (CAS No. 64-17-5) and 20 parts of deionized water were added, stirred for 0.5 h, and then 6 parts of dodecyltriethoxysilane (CAS No. 18536-91-9) were added, and the mixture was reacted for 6 h at 80° C. After the reaction was completed, the mixture was filtered, and the product was washed three times by centrifugation with anhydrous ethanol and vacuum dried at 60° C. for 12 h to obtain modified calcium silicate.
[0032] Preparation of anionic modified starch: 10 parts of α-starch (CAS No. 9005-84-9) and 15 parts of triethanolamine (CAS No. 102-71-6) were weighed by weight and added to 100 parts of deionized water, stirred and dissolved for 1 hour, and then 0.5 parts of epichlorohydrin (CAS No. 102-71-6) were added to react for 2 hours. After the reaction was completed, 6 parts of acrylic acid and 0.2 parts of ammonium persulfate were added, and the mixture was reacted at 70°C for 4 hours to obtain a starch mixture; 1 part of 3-sulfopropyl hexadecyldimethylammonium, 0.5 parts of calcium chloride, and 7.5 parts of epichlorohydrin were added to the starch mixture, and the mixture was reacted at 60°C for 10 hours. After the reaction was completed, the mixture was filtered and the filter residue was dried to obtain anionic modified starch.
[0033] Example 1
[0034] The present embodiment provides a foundry sand powder, which comprises, by weight: 70 parts of hydrophobic bentonite, 26 parts of coal powder, 10 parts of modified calcium silicate, and 8 parts of anionic modified starch.
[0035] The processing technology of casting sand powder includes the following steps:
[0036] The hydrophobic bentonite, coal powder, modified calcium silicate and anionic modified starch are sequentially added into a roller sand mixer to form a semi-finished product, and the mixture is obtained after stirring for 0.5 hours. The mixture is crushed into 300 meshes, and the crushed mixture is packaged to obtain molding sand powder for casting.
[0037] Example 2
[0038] The present embodiment provides a foundry sand powder, which comprises, by weight: 60 parts of hydrophobic bentonite, 15 parts of coal powder, 5 parts of modified calcium silicate, and 3 parts of anionic modified starch.
[0039] The processing technology of casting sand powder includes the following steps:
[0040] The hydrophobic bentonite, coal powder, modified calcium silicate and anionic modified starch are sequentially added into a roller sand mixer to form a semi-finished product, and the mixture is obtained after stirring for 0.2 hours. The mixture is crushed into 200 meshes, and the crushed mixture is packaged to obtain molding sand powder for casting.
[0041] Example 3
[0042] The present embodiment provides a foundry sand powder, which comprises, by weight: 65 parts of hydrophobic bentonite, 20 parts of coal powder, 8 parts of modified calcium silicate, and 5 parts of anionic modified starch.
[0043] The processing technology of casting sand powder includes the following steps:
[0044] The hydrophobic bentonite, coal powder, modified calcium silicate and anionic modified starch are sequentially added into a roller sand mixer to form a semi-finished product, and the mixture is obtained after stirring for 0.4 hours. The mixture is crushed into 250 meshes, and the crushed mixture is packaged to obtain molding sand powder for casting.
[0045] Example 4
[0046] The present embodiment provides a foundry sand powder, which comprises, by weight: 70 parts of hydrophobic bentonite, 26 parts of coal powder, 10 parts of calcium silicate, and 8 parts of anionic modified starch.
[0047] The processing technology of casting sand powder includes the following steps:
[0048] The hydrophobic bentonite, coal powder, calcium silicate and anionic modified starch are sequentially added into a roller sand mixer to form a semi-finished product, and the mixture is obtained after stirring for 0.5 hours. The mixture is crushed into 300 meshes, and the crushed mixture is packaged to obtain molding sand powder for casting.
[0049] Comparative Example 1
[0050] This comparative example provides a foundry sand powder, which comprises, by weight: 70 parts of bentonite, 26 parts of coal powder, 10 parts of calcium silicate, and 8 parts of α-starch.
[0051] The processing technology of casting sand powder includes the following steps:
[0052] Bentonite, coal powder, calcium silicate and α-starch are sequentially added into a roller sand mixer to form a semi-finished product, and a mixture is obtained after stirring for 0.5 hours. The mixture is crushed into 300 meshes, and the crushed mixture is packaged to obtain molding sand powder for casting.
[0053] Comparative Example 2
[0054] This comparative example provides a foundry sand powder, which comprises, by weight: 70 parts of hydrophobic bentonite, 26 parts of coal powder, 10 parts of calcium silicate, and 8 parts of α-starch.
[0055] The processing technology of casting sand powder includes the following steps:
[0056] The hydrophobic bentonite, coal powder, calcium silicate and α-starch are sequentially added into a roller sand mixer to form a semi-finished product, and the mixture is obtained after stirring for 0.5 hours. The mixture is crushed into 300 meshes, and the crushed mixture is packaged to obtain molding sand powder for casting.
[0057] Comparative Example 3
[0058] This comparative example provides a foundry sand powder, which comprises, by weight: 70 parts of bentonite, 26 parts of coal powder, 10 parts of modified calcium silicate, and 8 parts of α-starch.
[0059] The processing technology of casting sand powder includes the following steps:
[0060] Bentonite, coal powder, modified calcium silicate and α-starch are sequentially added into a roller sand mixer to form a semi-finished product, and a mixture is obtained after stirring for 0.5 hours. The mixture is crushed into 300 meshes, and the crushed mixture is packaged to obtain molding sand powder for casting.
[0061] Comparative Example 4
[0062] The present embodiment provides a foundry sand powder, which comprises, by weight: 70 parts of hydrophobic bentonite, 26 parts of coal powder, 10 parts of modified calcium silicate, and 8 parts of α-starch.
[0063] The processing technology of casting sand powder includes the following steps:
[0064] The hydrophobic bentonite, coal powder, modified calcium silicate and α-starch are sequentially added into a roller sand mixer to form a semi-finished product, and the mixture is obtained after stirring for 0.5 hours. The mixture is crushed into 300 meshes, and the crushed mixture is packaged to obtain molding sand powder for casting.
[0065] The properties of the molding sand powder provided in the above embodiments and comparative examples were tested, and the testing method was as follows:
[0066] Moisture content: Test according to the requirements of GB / T 2684-2009 Test methods for foundry sand and mixtures.
[0067] Compactness: Test according to the requirements of GB / T 2684-2009 Test methods for foundry sand and mixtures.
[0068] Green compressive strength: Tested in accordance with the requirements of GB / T 2684-2009 Test methods for foundry sand and mixtures.
[0069] The above performance test data is shown in Table 1.
[0070] Table 1 Performance test results
[0071] Water content (%) Compactness rate (%) Wet compressive strength (MPa) Example 1 1.5 49 98 Example 2 1.6 48 97 Example 3 1.5 48 98 Example 4 2.1 44 91 Comparative Example 1 2.8 38 81 Comparative Example 2 2.3 39 82 Comparative Example 3 2.2 39 81 Comparative Example 4 1.6 39 82
[0072] From the above content, it can be seen that the present invention uses hydrophobic bentonite, coal powder, silicate and starch as main components, modifies calcium silicate, and uses it together with anion-modified starch to obtain casting sand powder (Examples 1 to 3), which has a water content of 1.5 to 1.6%, a compaction rate of 48 to 49%, and a wet compressive strength of 97 to 98 MPa.
[0073] Compared with Example 1, if modified calcium silicate is not used, the water content increases, and the compaction rate and wet compressive strength decrease (Example 4); compared with Example 1, if anionic modified starch is not used, the compaction rate and wet compressive strength decrease (Comparative Example 4).
[0074] Comparative Example 1 does not adopt the technical innovation of the present invention, so the performance is poor, the water content is 2.8%, the compaction rate is 38%, and the wet compressive strength is 81Mpa; compared with Comparative Example 1, if hydrophobic bentonite is used, the water content decreases (Comparative Example 2); compared with Comparative Example 1, if modified calcium silicate is used, the water content decreases (Comparative Example 3).
[0075] In summary, the present invention adopts hydrophobic bentonite, coal powder, silicate and starch as main components, and modifies calcium silicate, and uses it together with anion-modified starch. By introducing hydrophobic components, the water content of the molding sand powder is effectively reduced, and the compaction rate is improved, ensuring that the strength of the molding sand powder can meet the requirements when used.
[0076] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A casting sand powder, characterized in that: The components include, by weight: 60-70 parts of hydrophobic bentonite, 15-26 parts of coal powder, 5-10 parts of silicate, and 3-8 parts of starch; The starch is anionic modified starch; The preparation method of the anionic modified starch is as follows: 10 parts of α-starch and 15 parts of triethanolamine are weighed by weight, added into 100 parts of deionized water, stirred and dissolved for 1 hour, then 0.5 parts of epichlorohydrin are added to react for 2 hours, and after the reaction is completed, 6 parts of acrylic acid and 0.2 parts of ammonium persulfate are added, and the mixture is reacted at 70° C. for 4 hours to obtain a starch mixture; 1 part of 3-sulfopropyl hexadecyldimethylammonium, 0.5 parts of calcium chloride and 7.5 parts of epichlorohydrin are added into the starch mixture, and the mixture is reacted at 60° C. for 10 hours, filtered after the reaction is completed, and the filter residue is dried to obtain the anionic modified starch.
2. The casting sand powder according to claim 1, characterized in that: The preparation method of the hydrophobic bentonite is: In parts by weight, 30 parts of bentonite and 5 parts of hexadecyltrimethylammonium bromide are added to 200 parts of deionized water, stirred evenly, and then oscillated at 150 r / min for 4 hours at 60° C. using a constant temperature digital oscillator. After the oscillation is completed, centrifugation is performed, and the centrifugal precipitate is dried at 50° C. for 12 hours and ground to obtain hydrophobic bentonite.
3. The casting sand powder according to claim 1, characterized in that: The silicate is selected from any one of magnesium silicate, calcium silicate, aluminum silicate, and iron silicate, or a combination of at least two of them.
4. The casting sand powder according to claim 3, characterized in that: The calcium silicate is modified calcium silicate.
5. The casting sand powder according to claim 4, characterized in that: The preparation method of the modified calcium silicate is: In parts by weight, 10 parts of acidified calcium silicate are added to 150 parts of anhydrous ethanol and dispersed evenly, then 30 parts of ammonia water and 20 parts of deionized water are added, stirred for 0.5 h, and then 6 parts of dodecyltriethoxysilane are added. The reaction is carried out at 80° C. for 6 h. After the reaction is completed, the product is filtered, washed three times by centrifugation with anhydrous ethanol, and vacuum dried at 60° C. for 12 h to obtain modified calcium silicate.
6. The casting sand powder according to claim 4, characterized in that: The preparation method of the acidified calcium silicate is: In parts by weight, 10 parts of calcium silicate are added to 100 parts of deionized water, stirred for 0.5 h to obtain a suspension, a hydrochloric acid solution with a mass concentration of 5% is added dropwise to the suspension, and the mixture is reacted for 2 h at a pH of 5. After the reaction is completed, the mixture is filtered and the filter residue is dried to obtain acidified calcium silicate.
7. A process for processing casting sand powder according to any one of claims 1 to 6, characterized in that: The steps include: The hydrophobic bentonite, coal powder, silicate and starch are sequentially added into a roller sand mixer to form a semi-finished product, and a mixture is obtained after stirring. The mixture is crushed into 200-300 meshes, and the crushed mixture is packaged to obtain molding sand powder for casting.
8. The process for processing casting sand powder according to claim 7, characterized in that: The stirring time is 0.2 to 0.5 h.
Citation Information
Patent Citations
Gas range
CA102716A
Alkali metal silicate binder compositions
KR1019810000572B1
Green sand composition for casting
US4137085A
Foundry mold and core sands
US4505750A